Mere Symbols - Herzfeld, Michael (Anthropologica, 2022)
Symbolism is not absent from modernity. Rather, the absence of an anthropological awareness of its presence favours semiotic manipulations that serve the interests of global domination, often in the name of populist policies. Within a framework broadly circumscribed by "Western" values, local and nationalist politicians exploit models of intimacy, kinship and engagement in ways that often undermine the interests of the marginal populations to which they most effectively appeal, especially when the rhetorics in question are not purely verbal and are thus more resistant to critical analysis. Examples are drawn primarily from Greece, Italy, Thailand, and the United States.